المعاقبة في الدرس النحوي : دراسة دلالية - ديرشوي، أحمد محمد عطوف
This research aims to study the phenomenon of ‘Al-Moa'aqabah’ in Arabic grammar, define its concept, clarify its meaning and grammatical characteristics, and semantically analyze its examples contained in grammarians' books. The importance of this phenomenon comes as it is as old as the Arabic language. This phenomenon prevails in the language of some Arab tribes, which are considered referential tribes by some grammarians. This phenomenon explains the semantic difference between words, such as ‘Riya’ (ريّا ) and ‘Rawa’ (روّى ); where the first is an adjective and the second is a noun. Therefore, this phenomenon was not arbitrary but was intended to show the semantics of the words, besides the phonetic significance of this phenomenon. This research uses both descriptive and analytical approaches by collecting definitions and explanations related to this phenomenon and analyzing its implications to arrive at the results. One of the most important results of this research is that ‘Al-Moa'aqabah’ indicates the circulation, alternation, and succession of something, where ‘Al-A'qeb’ (the successor) replaces its predecessor. ‘At-Ta'aqub’ is clearer than ‘Al-Moa'aqabah’ as it indicates accurate and continuous alternation of the words, just like the alternation of day and night. At-Ta'aqub’ that none of the sounds (the words) overcome or dominate the other; thus, both words have the same strength in terms of the permissibility of pronunciation and use. It turns out that the ancient grammarians were aware of the phenomenon ‘Al-Moa'aqabah’ and its origins. However, they used other terms that are synonymous in the linguistic sense, such as the ‘Al-Badal, ‘Al-Modara'ah’, ‘Al-Ilhak’, and others. This is because these terms are similar to ‘Al-Moa'aqabah’ in their linguistic meaning, which is succession and alternation.